Risk, return and cash flow characteristics of infrastructure fund investments - Florian Bitsch; Axel Buchner; Christoph Kaserer (EIB Papers, 2010)
We analyze the risk, return and cash flow characteristics of infrastructure investments by using a unique dataset of deals done by private equity-like investment funds. We show that infrastructure deals have a performance that is higher than that of noninfrastructure deals, despite lower default frequencies. However, we do not find that infrastructure deals offer more stable cash flows. Our study offers some evidence in favour of the hypothesis that higher infrastructure returns could be driven by higher market risk. In fact, these investments appear to be highly leveredand their returns are positively correlated to publicequity markets, but uncorrelated to GDP growth. Our results also indicate that returns could be influenced by the regulatory framework as well as by defective privatization mechanisms. By contrast, returns are neither linked to inflation nor subject to the 'money chasing deals' phenomenon.
Keywords: 330